2005
DOI: 10.1140/epjc/s2005-02378-6
|View full text |Cite
|
Sign up to set email alerts
|

Electroweak corrections uncertainty on the W mass measurement at LEP

Abstract: The systematic uncertainty on the W mass and width measurement resulting from the imperfect knowledge of electroweak radiative corrections is discussed. The intrinsic uncertainty in the 4-f generator used by the DELPHI Collaboration is studied following the guidelines of the authors of YFSWW, on which its radiative corrections part is based. The full DELPHI simulation, reconstruction and analysis chain is used for the uncertainty assessment. A comparison with the other available 4-f calculation implementing DP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Studies have shown [39] that the theoretical implementation of these corrections in RacoonWW [40] are in good agreement with YFSWW3. The following two possible contributions to the uncertainties in these corrections using YFSWW3 are considered.…”
Section: Next-to-leading O(α) Correctionsmentioning
confidence: 76%
“…Studies have shown [39] that the theoretical implementation of these corrections in RacoonWW [40] are in good agreement with YFSWW3. The following two possible contributions to the uncertainties in these corrections using YFSWW3 are considered.…”
Section: Next-to-leading O(α) Correctionsmentioning
confidence: 76%
“…Higher-order leading-log FSR corrections are included using PHOTOS for leptons and PYTHIA for quarks. ISR effects on m W are estimated by comparing the O(α 3 ) with the O(α 2 ) calculation, yielding small shifts of about 1 MeV [259]. The effect of Coulomb screening are estimated by taking half of the difference between Monte-Carlo samples with screened Coulomb effect and without any Coulomb effect, which amounts to about 7 MeV.…”
Section: Initial State Radiation and O(α) Effectsmentioning
confidence: 99%
“…In [35] this study has been performed in the context of the full Delphi simulation and analysis procedure; furthermore the main uncertainties due to non-CC03 4-fermion background events have been studied. Radiative corrections uncertainties on non 4-fermion background events are included in the uncertainty estimated on the background.…”
Section: Electroweak Radiative Correctionsmentioning
confidence: 99%